Pemanfaatan Artificial Intelligence dalam Pendidikan: Antara Transformasi Digital dan Krisis Karakter Siswa - Marinus Tanggu Holo; Andarweni Astuti (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
The rapid development of Artificial Intelligence (AI) technology presents significant opportunities for transforming educational practices: personalization, rapid formative feedback, and administrative efficiency. However, AI adoption in schools also brings challenges related to values, including the potential erosion of students' positive character: dependency on automated tools, tendencies toward plagiarism, weakening of moral obligations toward academic honesty, and diminished critical thinking skills regarding AI-generated content. This article conducts a conceptual study and policy literature review to (a) map the relationship between AI adoption and student character issues; (b) identify the factors contributing to the character crisis in AI utilization; and (c) formulate pedagogical intervention strategies, school policies, and research agendas to address these challenges. Key recommendations include integrating AI literacy and digital ethics into the curriculum, strengthening teacher capacity through practice-based training, designing policies that place humans in control of the learning process, and fostering collaboration between policymakers, education practitioners, and technology developers to ensure that AI enhances, rather than replaces, character development.